Gender and territory: conditions for the reproduction of life, politics public and participation of indigenous peasant women and women farmers in Ecuador - Aguinaga Barragán, Alba Margarita (2019)
This article provides a panoramic view of the situation of Ecuadorian indigenous and peasant women regarding their living conditions, the general impact of public policy, inclusion in national and international regulations and the dynamics of territorial participation. The diverse ecuadorian rural women have had a leading role between 2011 and 2015, in the context of the government of the Economist Rafael Correa, for their political and social role in the political debate of their rights, territory and defense of resources natural.During those years rural women live at the same time, a favorable impact of public policies for the social reproduction of life and precariousness indicators that show the social and economic exclusion and therefore the difficulty of reaching the levels optimal equity compared to the State and society.